The impact of various strength training protocols on the strength and sporting performance of junior male judokas - Osipov, A. Y.; Slizik, M.; Bartik, P.; Kudryavtsev, M. D.; Iermakov, S. S. (Archives of Budo, 2021)
Background and Study Aim: Judo coaches offer various strength training protocols to improve performance of judo athletes. The purpose of the study was knowledge about the impact of a 12-week various strength training protocols on the strength and sporting performance of junior male judo athletes. Material and Methods: The participants 17 years old elite male judokas (n = 36). The overall study period was 12 week. Various strength training protocols were used. The group 1 used resistance workouts (four workouts per week). Other participants used different protocols of mixed strength workouts: two resistance + two circuit workouts per week (group 2) and three CrossFit + one resistance workout per week (group 3). The general (IHST, Bench Press, Back Squat, Squat Jump) and specific (SJFT and Sporting Performance) tests to assess for strength performance of athletes were used. Results: A higher (p=0.05) positive impact of various strength training protocols for studied athletes on back squat test (group 1) and on the pull-up test (group 3) was found. A more significantly (p=0.05) positive impact of resistance workouts and strength mixed (CrossFit + resistance) workouts on a sporting performance (won competitive judo matches) of studied judo athletes (group 1 and group 3) was found.